Eschatological salvation in Hebrews 1:5-2:5 - Oyetade, M. O. (Ilorin journal of religious studies, 2013)
Salvation which is an indispensable element in all religions, is provided in one way in both OT and NT, and also rooted in grace, faith and sacrifice. This same salvation has past, present and future dimensions. The eschatology which is from two Greek words- and means a study of last things which future aspect of salvation addresses. Methodologies adopted in this paper were historical and exegetical. The historical method was used in order to reconstruct the past both in biblical times and in the 21st century Church. The exegetical method was for a comprehensive examination of both the content and the context to enhance better interpretation of the relevant text. Data were gathered through secondary sources in which consultations were made through published works and the internet. It has been established in this paper that eschatology is essential to salvation and that without the completion or consummation of the eschatological prophesies salvation is not complete. By implication therefore, Christians are warned against loosing the future salvation by a careless inattention to the contexts of Hebrews 9:28 or practice in daily life, a text which focuses both on Christ¡¦s death and return. Therefore, the eschatological connection with salvation is incontrovertible.